INDUSTRIAL ESPIONAGE - Mukwevho, Humbulani Seth (My University, 2011)
This was an exploratory research project whose purpose was to analyze the risk of industrial espionage in the corporate environment and develop a business security framework. The study analyzed aspects of industrial espionage in the international environment with a view of adopting best practices for the benefit of corporate South Africa. The study used qualitative research methods and thematic analysis to assess data derived from primary and secondary sources. The results of the research process revealed that industrial espionage is a major business risk, and is perpetrated by a number of means and methods, including human and technical intelligence. The business security framework developed for the study consists of a multilayer compendium that includes both modern and traditional applications
MM - P&DM
Keywords: Industrial espionage